Experimental study on radial gravity currents flowing in a vegetated channel. (25th February 2022) - Petrolo, D.; Ungarish, M.; Chiapponi, L.; Longo, S.
Abstract: Abstract : We present an experimental study of gravity currents in a cylindrical geometry, in the presence of vegetation. Forty tests were performed with a brine advancing in a fresh water ambient fluid, in lock release, and with a constant and time-varying flow rate. The tank is a circular sector of angle 30^° with radius equal to 180 cm. Two different densities of the vegetation were simulated by vertical plastic rods with diameter D=1.6 cm . We marked the height of the current as a function of radius and time and the position of the front as a function of time. The results indicate a self-similar structure, with lateral profiles that after an initial adjustment collapse to a single curve in scaled variables. The propagation of the front is well described by a power law function of time. The existence of self-similarity on an experimental basis corroborates a simple theoretical model with the following assumptions: (i) the dominant balance is between buoyancy and drag, parameterized by a power law of the current velocity |u|^λ-1u ; (ii) the current advances in shallow-water conditions; and (iii) ambient-fluid dynamics is negligible. In order to evaluate the value of λ (the only tuning parameter of the theoretical model), we performed two additional series of measurements. We found that λ increased from 1 to 2 while the Reynolds number increased from 100 to approximately 6×10^3, and the drag coefficient and the transition from λ=1 to λ=2 are quantitatively affected by D, but the structure of the model is not.